Empowering aspects for healthy food and physical activity habits: adolescents' experiences of a school-based intervention in a disadvantaged urban community. (4th June 2018) - Holmberg, Christopher; Larsson, Christel; Korp, Peter; Lindgren, Eva-Carin; Jonsson, Linus; Fröberg, Andreas; Chaplin, John E; Berg, Christina
ABSTRACT: Purpose: This study aimed to describe adolescents' experiences of participating in a health-promoting school-based intervention regarding food and physical activity, with a focus on empowering aspects. Method: The school was located in a urban disadvantaged community in Sweden, characterized by poorer self-reported health and lower life expectancy than the municipality average. Focus group interviews with adolescents (29 girls, 20 boys, 14–15 years) and their teachers (n = 4) were conducted two years after intervention. Data were categorized using qualitative content analysis. Results: A theme was generated, intersecting with all the categories: Gaining control over one's health: deciding, trying, and practicing together, in new ways, using reflective tools. The adolescents appreciated influencing the components of the intervention and collaborating with peers in active learning activities such as practicing sports and preparing meals. They also reported acquiring new health information, that trying new activities was inspiring, and the use of pedometers and photo-food diaries helped them reflect on their health behaviours. The adolescents' experiences were also echoed by their teachers. Conclusions: To facilitate empowerment and stimulate learning, health-promotion interventions targeting adolescents could enable active learning activities in groups, by using visualizing tools to facilitate self-reflection, and allowing adolescents to influence intervention activities.